Influence of Reinforcement Corrosion on Reliability of Existing Concrete Structures - Kotes, Peter; Vican, Josef; Slavik, Jiri (Communications - Scientific letters of the University of Zilina, 2001)
The quality and the durability of the concrete structures are affected by lots of degradation processes. The paper deals with reinforcement corrosion and its influence on the reliability of the existing concrete structures. Two types of passive stage calculation and two types of active stage calculation are considered in this paper. The probabilistic approach is used for the time dependent resistance solution. In conclusion, the change of the failure probability and reliability index of the structure in time influenced by reinforcement corrosion are shown.